Correlation Mother’s Eduaction and Received Stunting Information with Mother’s Stunting Knowledge - Ayyida Aini Rahmah; Desy Indra Yani; Theresia Eriyani; Laili Rahayuwati (Universitas Padjadjaran, 2023)
Inadequate nutritional intake in toddlers is one of the main causes of stunting. Mother’s knowledge will determine attitudes in maintaining the nutritional needs of toddlers, and reducing the potential for stunting in toddlers. Factors that influence knowledge are education and information. The aim of the study was to analyze the correlation between mother’s education level and received stunting information with mother’s knowledge of stunting in Desa Sukamulya, Bandung Regency. The research design is a correlational quantitative, secondary data approach. The population is mothers with toddler in Desa Sukamulya, Bandung Regency. Samples were taken using total sampling technique, totaling 55 people. The instrument consisted of mother’s education, received stunting information, and mother’s stunting knowledge. The statistical test will be used Chi square. The results showed that there was no correlation between the mother’s education level (p-value = 0.138) and information exposure (p-value = 1.000) and the mother’s knowledge of stunting. Implementation of health education with audio-visual media and booklets as well as information guidance through health cadres can be carried out by community nurses to increase public knowledge regarding stunting. Education level and information exposure were not related to knowledge about stunting in Sukamulya Village, Bandung Regency. Community knowledge can be increased through the provision of health education interventions. Further research still needs to be done with better methods by use primary data.